The Significance of the Development of the Salted Fish Industry for Community Economic Growth from an Islamic Economic Perspective (Study on Baai Island, Kampung Melayu, Bengkulu City) - Yuyun Novia Sari; Herlina Yustati; Idwal B (Yayasan Darussalam Bengkulu, 2024)
This research was conducted on Baai Island, Malay Village, Bengkulu City. The purpose of this study was to determine the Significance of the Development of the Salted Fish Industry for the Growth of the Community Economy in the Perspective of Islamic Economics. This research is qualitative. Data collection methods through interviews with sellers, workers, and buyers of salted fish in the baai island area. Based on the formulation of the problem in this study, namely: How is the development of the Baai Island salted fish processing industry and how is the impact of the development of the Baai Island salted fish industry on the economy of the community in the perspective of Islamic Economics? The research findings show that the business development carried out is through 2 methods online and in person. The impact of the development of this industry itself is the increased income of the community, the welfare of the Baai Island community, and the fulfilled needs of life.